Cash Holding in Companies Registered on the Jakarta Islamic Index: Analysis of Net Working Capital Factors, Levels of Leverage, and Levels of Profitability - Rizqia Wildiany; A. Jajang W. Mahri; Suci Apriliani Utami (Indonesian Journal of Economics and Management, 2022)
Inaccuracy in determining the optimal cash holding level can cause the company's activities to be disrupted and even unable to run, holding too little cash will have a negative impact on the company, which can cause a company to go bankrupt, and vice versa, if the amount of cash is too much will cause unproductive cash because cash is idle fund. This study aims to analyze net working capital, level of leverage, and level of profitability of cash holdings. The population of this study is all companies listed on the Jakarta Islamic Index for the 2016-2021 period. The sample of this research is 15 companies taken by purposive sampling technique. The data analysis technique used in this study was panel data regression analysis using Eviews 10 software. The results showed that the net working capital variable had no effect on cash holdings. While the leverage level variable has a negative effect on cash holding and the profitability level variable has a positive effect on cash holding. Recommendations for companies listed on the Jakarta Islamic Index are expected to increase cash holdings, for future researchers it is better to add other variables that can be factors that affect the company's cash holdings.